2022
DOI: 10.3390/genes13122261
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Evaluation of Bread Wheat (Triticum aestivum L.) Genotypes for Stay Green under Drought Stress

Abstract: Water availability is considered as the main limiting factor of wheat growth illuminating the need of cultivars best adapted to drought situations for better wheat production and yield. Among these, the stay-green trait is thought to be related to the ability of wheat plants to maintain photosynthesis and CO2 assimilation, and a detailed molecular understanding of this trait may help in the selection of high-yielding, drought-tolerant wheats. The current study, therefore, evaluated the physiological responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…81 Photosynthesis in plants is controlled by various aspects including light, water, temperature, carbon dioxide, soil pH, and availability of nutrients, which interact directly or indirectly by changing the chemical and enzymatic procedures of photosynthesis in various plants. 95,96 In the present research, the photosynthetic pigments were remarkably increased under the applied foliar treatment of Cu and B alone and along with T. harzianum. Results of the current research are in general agreement with those of ref 93.…”
Section: Discussionsupporting
confidence: 50%
“…81 Photosynthesis in plants is controlled by various aspects including light, water, temperature, carbon dioxide, soil pH, and availability of nutrients, which interact directly or indirectly by changing the chemical and enzymatic procedures of photosynthesis in various plants. 95,96 In the present research, the photosynthetic pigments were remarkably increased under the applied foliar treatment of Cu and B alone and along with T. harzianum. Results of the current research are in general agreement with those of ref 93.…”
Section: Discussionsupporting
confidence: 50%
“…However, still, their function is not fully understood. GLPs are expressed in all types of tissues (flowers, seeds, roots, stems, leaves, and embryos) by playing a pivotal role against diverse environmental stresses. , Previously, among abiotic stresses, they were found effective against heavy metals, , drought, , salt, , desiccation, heat, , abscisic acid (ABA), and UV radiation acclimation mediated by methylation in the promoter region as observed in rice . Among biotic stresses, they were active against herbivore-induced damage, Sclerotinia sclerotiorum (S.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in photosynthetic pigments and subsequently in chlorophyll fluorescence attributes may lead to an alteration in photosynthetic efficiency, including the capability to harvest light; hence, observing these traits is essential to determine the plant photosynthetic effectiveness. In the current research, a differential trend was observed in the chlorophyll content, which was positive in the case of plants primed with tap water and Fe-10 mM, which may be attributed to simultaneous changes in osmoprotectant and different response levels of the studied wheats. − …”
Section: Discussionmentioning
confidence: 46%